Connotations, Components and Development of Teachers' Scientific Literacy - WANG Xianping; MAI Huijun; ZHU Guojing (Jiaoshi jiaoyu xuebao)
Teachers'scientific literacy is a key factor in responding to the new round of scientific and technological revolution and industrial change, cultivating scientific and technological innovation talents and enhancing the scientific literacy of all people. From the view of the characteristics of teachers'work, teachers'scientific literacy contains both dynamic and static levels. The static level means that teachers should have basic scientific knowledge, scientific spirit and attitude while the dynamic level implies that teachers should also have the method and ability to foster students' scientific literacy. Therefore, teachers'scientific literacy presents unique characteristics of education, dynamics, and systematicity. Through the analysis of the connotations and characteristics of teachers' scientific literacy, the framework model of the components of teachers'scientific literacy isrevised twice with the help of expert consultation.Then the framework of teachers'scientific literacy consists of three dimensions, which are scientific spirit and educational awareness, scientific cognition and educational ability, and scientific method and teaching and research skills. It is suggested that teachers'scientific literacy and education ability should be enhanced through such paths as fine-tuning policy, concreting the conceptualization of teachers'scientific literacy, optimizing cultivation initiatives to realize the "embeddedness" of pre-service teachers'scientific literacy, updating the content and form of training to support the continuous improvement of post-service teachers'scientific literacy, providing scientific and cultural support to create an environment for the development of teachers'scientific literacy.